2018
DOI: 10.1128/jvi.00197-18
|View full text |Cite
|
Sign up to set email alerts
|

Host Factor SPCS1 Regulates the Replication of Japanese Encephalitis Virus through Interactions with Transmembrane Domains of NS2B

Abstract: Signal peptidase complex subunit 1 (SPCS1) is a newly identified host factor that regulates flavivirus replication, but the molecular mechanism is not fully understood. Here, using Japanese encephalitis virus (JEV) as a model, we investigated the mechanism through which the host factor SPCS1 regulates the replication of flaviviruses. We first validated the regulatory function of SPCS1 in JEV propagation by knocking down and knocking out endogenous SPCS1. The loss of SPCS1 function markedly reduced intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…The interaction of virus and host factors is a key step for the virus infection process and plays an important role in viral RNA replication, translation, and post-translational modification, aiding in our understanding of the molecular mechanism of viral pathogenesis and the development of antiviral drugs [38]. In recent years, several studies have identified anti-JEV host restriction factors with different mechanisms [17,39,40,41,42,43,44,45]. In this study, host cellular protein ILF2 was identified to specifically interact with JEV NS3.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of virus and host factors is a key step for the virus infection process and plays an important role in viral RNA replication, translation, and post-translational modification, aiding in our understanding of the molecular mechanism of viral pathogenesis and the development of antiviral drugs [38]. In recent years, several studies have identified anti-JEV host restriction factors with different mechanisms [17,39,40,41,42,43,44,45]. In this study, host cellular protein ILF2 was identified to specifically interact with JEV NS3.…”
Section: Discussionmentioning
confidence: 99%
“…The particle and NC assembly processes do not solely rely on viral proteins. In JEV-infected cells, transmembrane domains of NS2B interact with the host factor SPCS1 to secure particle production and in DENV infections, the interaction of C protein and nucleolin is essential for formation of virions [ 141 , 142 ]. Additionally, WNV particle production requires the presence of the host helicase DDX56 at the viral assembly sites [ 143 , 144 ].…”
Section: Life Cyclementioning
confidence: 99%
“…The BiFC assay was performed according to a previous study (Ma et al, 2018). Briefly, HEK-293T cells grown in 24 well plates were transiently co-transfected with combinations of plasmids VC-PB2 (500 ng) and VN-eIF4A3 (500 ng), or VC-PB2 (500 ng) and VN-vector (500 g) and incubated at 37°C for 24 h. Fluorescence emission was detected using a fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%